KOMUNIKASI PERSUASIF PENGURUS ORGANISASI SEPAK BOLA DALAM PEMBINAAN ETIKA DUKUNGAN KELOMPOK SUPORTER FANATIK KLUB SEPAK BOLA NASIONAL - Muhammad Haikal, Khan; Naryoso, Agus (Interaksi Online, 2019)
This study was done based on the poor ethical peformance of the Indonesian Football League supporters at giving the support to their favorite team, that leads to the both parties (supporters or football team) got negative consequences whether in a form of fining or suspension. This study aims to find out and analyze persuasive communication carried out by the management of the football club organization in fostering the ethical support of the fanatical support group. This study took the research subject of organizational management from PSIS Semarang and PSIM Jogja. PSIS Semarang was chosen because it is famous for League 1 clubs that have two groups of fanatical supporters, while PSIM Jogja was chosen because it is one of the oldest clubs in Indonesia. This research is a descriptive qualitative study that uses case studies as a research method with match pattern analysis as its analysis technique. The results of this study show how to compile persuasive messages, administrators of ball organizations use conventional logic and rhetorical logic. Rhetoric logic become the logical thinking of organizational management when meeting directly with supporter groups, while conventional logic becomes the logic of organizational management thinking on messages on social media. The rhetoric logic that is often used raises messages that show the position of the organization's management of the position of the relationship in obtaining coordination. This power of relationship position also influences the persuasive communication techniques used by the management of the organization. The technique of emotional attraction in persuasive communication by the organizers of soccer organizations is the one most often used. The emotional side that is most often used is to express the club's problems that must be paid for the reasons that are worse than the group of supporters. In addition to emotional attractiveness, the attraction of fear is also used by the organizers of the organization in fostering the ethics of the support of its supporters. The fear of the club will face difficulties and losses due to the act of the support group making supporters group think again to take actions that have been approved by the PSSI. For the sake of becoming a professional club, the club of course runs the rules of the AFC to foster good relations with the group of supporters.